Banking Sector Fragility and Systemic Sources of Fragility - Gonzalez-Hermosillo, Brenda (IMF Working Papers; Working Paper ;, 1996)
A theoretical framework to assess the degree of fragility or, inversely, the soundness of the banking system is proposed. It is argued that, while a bank may be either solvent or insolvent at any given time, its degree of fragility must be a forward-looking measure based on the probability that it can withstand a destabilizing shock. Externalities are particularly important because they can constitute a serious source of systemic risk. The factors that determine banks' soundness can be separated into bank-specific and those common to all banks (subject to microprudential and macroprudential considerations, respectively). The interconnection between banking crises and currency crises (in both directions) is also discussed.